2013
DOI: 10.1519/jsc.0b013e318291b29f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Aerodynamic Helmet on Head Temperature, Core Temperature, and Cycling Power Compared With a Traditional Helmet

Abstract: Nonvented "aerodynamic helmets" reduce wind resistance but may increase head (Th) and gastrointestinal (Tgi) temperature and reduce performance when worn in hot conditions. This study tested the hypothesis that Th and Tgi would be greater during low-intensity cycling (LIC) in the heat while wearing an aero helmet (AERO) vs. a traditional vented racing helmet (REG). This study also tested the hypothesis that Th, Tgi, and finish time would be greater, and power output would be reduced during a self-paced time tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…These results are supported by previous investigations examining the effect of vented helmets on heat dissipation and physiological strain (Holland et al 2002;Lee et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results are supported by previous investigations examining the effect of vented helmets on heat dissipation and physiological strain (Holland et al 2002;Lee et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…5). This diverges from the results of Lee et al whose 2013 study found no differences in power output between a vented standard bicycle helmet and an unvented aerodynamic helmet during a 12-km cycling time trial (Lee et al 2013). Their shorter study duration in combination with higher power outputs (%VO 2max ) and higher ambient temperatures may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Dadurch lassen sich Fragen beantworten wie jene, ob ein aerodynamischerer, jedoch schlecht belüfteter Helm einem gut belüfteten Helm vorgezogen werden soll oder wie sich neue Belüftungskonzepte für aerodynamische Fahrradhelme auswirken. Die erstere Fragestellung wurde mit Studienteilnehmern für ein Kurzdistanzzeitfahren über 12 km untersucht . Dabei ergaben sich für den schlechter belüfteten, jedoch aerodynamischeren Helm eine um 0,4 °C erhöhte Kopftemperatur sowie eine um 0,2 °C erhöhte Körperkerntemperatur, verglichen mit dem gut belüfteten Helm.…”
Section: Gekoppeltes Modellunclassified